Reshaping educational spaces: An emerging framework for place-making and belonging in higher education with practical considerations for the classroom - Poppendorf, Alexandria (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
This paper explores place-making and belonging in higher education through a framework rooted in Indigenous relational ethics, posthuman philosophy, and autobiographical narrative. It examines how settler colonial legacies shape educational spaces and proposes strategies for fostering inclusive, ethical, and communal learning environments. Emphasizing epistemology, methodology, axiology, and ontology, the framework encourages critical reflection, experiential learning, reciprocity, and collaborative knowledge webs. It invites educators to reimagine classrooms as living, relational spaces where all beings can feel valued, connected, and empowered.